PHYSICAL ACTIVITY TO WIN MEMORY AND INTELLIGENCE: THE BENEFITS OF BRAIN-DERIVED NEUROTROPHIC FACTOR (BDNF). (Fiep Bulletin - online, 2011)
The human body secretes a substance called daily-derived neurotrophic factor that is responsible for activating the hypothalamus (responsible for memory both long and short term). Living things can increase the amount of brain-derived neurotrophic factor secreted by day practicing sports, specifically rapid and intense exercise. By practicing this exercise on a continuous levels of cortisol (hormone responsible for stress), increases the neuronal synapses, the synthesis of glutamate (the principal excitatory neurotransmitter of the nervous system and decreases the GABA (the major inhibitory neurotransmitter). Thanks to all the properties given neurotrophic factor and the result is a decrease in stress levels, increased concentration, increased memory and short-and long-term neuronal plasticity, not to mention an increase in levels CI To see all of the above study was conducted in the Greenland Fitness with a mixed group study of 25 people aged 20 to 30 years, which was submitted to a special routine of exercises and three IQ test as a result it was observed that without exception all participants increased their level of CI and its concentration by rapid and intense routine of exercises.
Keywords: Derived neurotrophic factor – intelligence – neuronal plasticity